KONTRIBUSI PT. BCP (BULUH CAWANG PLANTATION) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT PERSPEKTIF EKONOMI ISLAM DI DESA MENTIBAR KECAMATAN PALOH - fitri fitri; wahab; Ahmad Yasir (Cross-Border Journal of Business Management, 2023)
This study uses a descriptive qualitative approach with a sample of 20 Mentibar Village residents, Village Leaders and Heads, and is a type of field research. Data collection techniques used are observation, interviews and documentation. The data used in the form of primary data are people who work at PT. BCP (Buluh Cawang Plantation), Leaders and Head of Mentibar Village, Secondary data obtained from various journals, articles, theses and other sources. The data analysis technique used is data reduction, data display and conclusion drawing. Data validity techniques used are triangulation and Member Check. The results of the research and discussion that have been carried out are related to the contribution of PT. BCP (Buluh Cawang Plantation) in improving the welfare of the community from an Islamic economic perspective in Mentibar Village, Paloh District, the following conclusions can be drawn: The contribution made by PT. BCP (Buluh Cawang Plantation) is very good. The form of contribution given by PT. BCP (Buluh Cawang Plantation) physical assistance and natural disaster assistance. Meanwhile, the Islamic Economics Review of the contributions made by PT. BCP (Buluh Cawang Plantation) for the community, there are several parts that have been contributed, such as Nurturing the Soul and Nurturing. Meanwhile, improving the welfare of society is in accordance with an Islamic economic perspective because it has achieved the goals of Islamic economics, namely realizing human goals to achieve world happiness and prosperity.